Communication perspectives on social networking and citizen journalism challenges to traditional newspapers - James E. Katz (International Telecommunications Society (ITS), 2011)
Communication perspectives are presented on the challenges posed to traditional newspapers by social media and citizen journalism, with special reference to the United States. This is an important topic given the critical role investigative reporting, long the domain of newspapers, plays in fostering democratic practices. New Media and social networking technology are evaluated in terms of their impact on the newspaper enterprise. Alternative scenarios for future developments are examined as are the implications for social values and the role of an informed citizenry in democratic society. Strategic management issues are analyzed, and the possibility is considered that social media can fulfill much of the democracy-enhancing role served traditionally by newspapers.
Keywords: O3; O30; O33; 330; Newspapers; news industry; social media; social networks; democracy; journalism